ip100802_elic_NominalForms_mezo_2 - Ирина Пайковна Кошкарёва (Туглакова); Олеся Ханина (Bernard Comrie, 2010)
О.Ханина собирает с И.П.Кошкаревой основные формы существительного глухочередующегося класса mezo 'чум' (см. набор форм в NounInflection_tundra_ToDo2010.doc), часть 2 O.Khanina collects with I.P.Koshkarjova main forms of a devoiced alternating noun noun mezo 'chum' (see the list of forms in NounInflection_tundra_ToDo2010.doc), part 2 Language_Name: Enets Language_Region: Asia Language_Country: Russia Project_Status: Complete Year: 2007 Start_Date: 2008-02-01 End_Date: 2011-01-31 Title ip100802_elic_NominalForms_mezo_2